Enhancement of polycrystalline silicon solar cells efficiency using indium nitride particles - ALEVLİ, MUSTAFA (IOP PUBLISHING LTD, 2015)
In this work, we present a hybrid indium nitride particle/polycrystalline silicon solar cell based on 230 nm size indium nitride particles (InN-Ps) obtained through laser ablation. The solar cell performance measurements indicate that there is an absolute 1.5% increase (Delta eta) in the overall solar cell efficiency due to the presence of InN-Ps. Within the spectral range 300-1100 nm, improvements of up to 8.26% are observed in the external quantum efficiency (EQE) and increases of up to 8.75% are observed in the internal quantum efficiency (IQE) values of the corresponding solar cell. The enhancement in power performance is due to the down-shifting properties of the InN-Ps. The electrical measurements are supplemented by TEM, Raman, UV/VIS and PL spectroscopy of the InN-Ps.
Keywords: particles; solar cell; enhancement; external quantum efficiency; internal quantum efficiency; efficiency; indium nitride; POROUS-SILICON; LASER-ABLATION; INN; PRESSURE; NANOCRYSTALS